Synergy-Dependent Center-of-Mass Control Strategies During Sit-to-Stand Movements - Simone Ranaldi; Leonardo Gizzi; Giacomo Severini; Cristiano De Marchis (IEEE Open Journal of Engineering in Medicine and Biology, 2025)
The characterization, through the concept of muscle synergies, of clinical functional tests is a valid tool that has been widely adopted in the research field. While this theory has been exploited for a description of the motor control strategies underlying the biomechanical task, the biomechanical correlate of the synergistic activity is yet to be fully described. In this paper, the relationship between the activity of different synergies and the center of mass kinematic patterns has been investigated; in particular, a group of healthy subjects has been recruited to perform simple sit-to-stand tasks, and the electromyographic data has been recorded for the extraction of muscle synergies. An optimal model selection criterion has been adopted for dividing the participants by the number of synergies characterizing their own control schema. Synergistic activity has then been mapped onto the phase-space description of the center of mass kinematics, investigating whether a different number of synergies implies the exploration of different region of the phase-space itself. Results show how using an additional motor module allow for a wider trajectory in the phase-space, paving the way for the use of kinematic feedback to stimulate the activity of different synergies, with the aim of defining synergy-based rehabilitation or training protocols.